2019
DOI: 10.3847/2041-8213/aaff6e
|View full text |Cite
|
Sign up to set email alerts
|

The Induced Global Looping Magnetic Field on Mars

Abstract: Magnetic fields inconsistent with draped IMFs and crustal fields have been observed on Mars.Considering the discovery of a global looping magnetic field around the Venusian magnetotail and the similarities in the solar wind interactions between Mars and Venus, we use MAVEN observations to investigate the global looping field on Mars and its formation mechanism. It is found that a global looping field also exists on Mars; therefore, this type of global looping field is a common feature of unmagnetized planetary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 44 publications
7
41
0
Order By: Relevance
“…A closed field configuration arises in the E − hemisphere. According to the hybrid simulations (see also Chai et al, ), the field lines passing Mars in the E + hemisphere can also reconnect with the formation of the closed loops.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A closed field configuration arises in the E − hemisphere. According to the hybrid simulations (see also Chai et al, ), the field lines passing Mars in the E + hemisphere can also reconnect with the formation of the closed loops.…”
Section: Discussionmentioning
confidence: 95%
“…Here we observe some new features probably missed in the averaged picture obtained from the observations. Besides the clockwise rotation of the B yz vector in the center of the tail (r <∼ 1R M ) caused by draping features in the transverse direction and a reversal of the B y component in the E − hemisphere, described by as a "looping" by Chai et al (2019), we also observe that signatures of Hall currents are appearing in the thin central current sheet at Z ∼ 1-1.3 R M (Figure 3b Figures 5c, 5d, and 5f depict maps of the magnetic field and the velocity of the planetary protons obtained by the hybrid simulations with the same input parameters as in Figure 3. In the E + hemisphere a common draping of the IMF over the ionosphere occurs.…”
Section: Observations and Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chai et al. (2019) found that there is a global induced looping field on Mars which are associated with heavy ion plumes.…”
Section: Introductionmentioning
confidence: 99%